Dietary fructose aggravates the pathobiology of traumatic brain injury by influencing energy homeostasis and plasticity. Issue 5 (May 2016) - Agrawal, Rahul; Noble, Emily; Vergnes, Laurent; Ying, Zhe; Reue, Karen; Gomez-Pinilla, Fernando
Fructose consumption has been on the rise for the last two decades and is starting to be recognized as being responsible for metabolic diseases. Metabolic disorders pose a particular threat for brain conditions characterized by energy dysfunction, such as traumatic brain injury. Traumatic brain injury patients experience sudden abnormalities in the control of brain metabolism and cognitive function, which may worsen the prospect of brain plasticity and function. The mechanisms involved are poorly understood. Here we report that fructose consumption disrupts hippocampal energy homeostasis as evidenced by a decline in functional mitochondria bioenergetics (oxygen consumption rate and cytochrome C oxidase activity) and an aggravation of the effects of traumatic brain injury on molecular systems engaged in cell energy homeostasis (sirtuin 1, peroxisome proliferator-activated receptor gamma coactivator-1alpha) and synaptic plasticity (brain-derived neurotrophic factor, tropomyosin receptor kinase B, cyclic adenosine monophosphate response element binding, synaptophysin signaling). Fructose also worsened the effects of traumatic brain injury on spatial memory, which disruption was associated with a decrease in hippocampal insulin receptor signaling. Additionally, fructose consumption and traumatic brain injury promoted plasma membrane lipid peroxidation, measured by elevated protein and phenotypic expression of 4-hydroxynonenal. These data imply that high fructose consumption exacerbates the pathology of brain trauma by further disrupting energy metabolism and brain plasticity, highlighting the impact of diet on the resilience to neurological disorders.